Australian songbird body size tracks climate variation: 82 species over 50 years. Issue 1916 (27th November 2019) - Gardner, Janet L.; Amano, Tatsuya; Peters, Anne; Sutherland, William J.; Mackey, Brendan; Joseph, Leo; Stein, John; Ikin, Karen; Little, Roellen; Smith, Jesse; Symonds, Matthew R. E.
Abstract : The observed variation in the body size responses of endotherms to climate change may be explained by two hypotheses: the size increases with climate variability ( the starvation resistance hypothesis ) and the size shrinks as mean temperatures rise ( the heat exchange hypothesis ). Across 82 Australian passerine species over 50 years, shrinking was associated with annual mean temperature rise exceeding 0.012°C driven by rising winter temperatures for arid and temperate zone species. We propose the warming winters hypothesis to explain this response. However, where average summer temperatures exceeded 34°C, species experiencing annual rise over 0.0116°C tended towards increasing size. Results suggest a broad-scale physiological response to changing climate, with size trends probably reflecting the relative strength of selection pressures across a climatic regime. Critically, a given amount of temperature change will have varying effects on phenotype depending on the season in which it occurs, masking the generality of size patterns associated with temperature change. Rather than phenotypic plasticity, and assuming body size is heritable, results suggest selective loss or gain of particular phenotypes could generate evolutionary change but may be difficult to detect with current warming rates.